1990
DOI: 10.1021/ac00218a007
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescent method for continuous monitoring of nitrous acid in ambient air

Abstract: A continuous-flow method for measuring atmospheric HNO2 concentration in real time has been developed that uses a chemiluminescent NOx monitor. A Na2CO3 solution strips gaseous HNO2 from the atmosphere by means of pulling an air sample and the solution through a glass coil and mixing continuously with ascorbic acid solution which reduces nitrite to NO. The mixture is led into a gas-liquid separating coil consisting of microporous PTFE tubing. The NO evolved from the separating coil is swept out by a stream of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 26 publications
3
12
0
1
Order By: Relevance
“…The decreasing trend for the HNO2 output was similar to those of NO and SO2, but the output was not in inverse proportion to the purge gas-flow rate. An identical result was obtained in our previous continuous-generation system for HNO2 vapor, 6 which was based on a bubbling technique, where the purge gas passed through a mixture of NaNO2 and H2SO4 solutions. In this system, the purge gas-flow rate was found to significantly affect the purity of the output as well as the HNO2 output, and working at high flow rates of purge gas was found to be advantageous for an efficient generation of high-purity HNO2.…”
Section: Output Characteristicssupporting
confidence: 79%
See 3 more Smart Citations
“…The decreasing trend for the HNO2 output was similar to those of NO and SO2, but the output was not in inverse proportion to the purge gas-flow rate. An identical result was obtained in our previous continuous-generation system for HNO2 vapor, 6 which was based on a bubbling technique, where the purge gas passed through a mixture of NaNO2 and H2SO4 solutions. In this system, the purge gas-flow rate was found to significantly affect the purity of the output as well as the HNO2 output, and working at high flow rates of purge gas was found to be advantageous for an efficient generation of high-purity HNO2.…”
Section: Output Characteristicssupporting
confidence: 79%
“…Because the converter efficiently reduces not only NO2 but also HNO2 to NO, it allows sequential measurements of NO and the sum (NO + NO2 + HNO2) by bypassing and passing through the converter, respectively. Our previous results 6 showed that HNO2 is quantitatively removed from the gas stream by a single Na2CO3-impregnated cellulose filter. This implies that the sum measured by passing through the Na2CO3-filter provides NOx (NO + NO2).…”
Section: Measurements Of No Hno2 and So2mentioning
confidence: 92%
See 2 more Smart Citations
“…Another method, the wetted wall denuders, has been presented in the last years [Vecera and Dasgupta, 1991;Simon and Dasgupta, 1995]. A continuous method based on the conversion of nitrite to NO followed by a detection by chemoluminescence has also been used [Kanda and Taira, 1990]. These methods are user-friendly and relatively inexpensive, but special care has to be taken to avoid cross sensitivities with other atmospheric species; therefore they require much experimental work [Febo et al, 1993].…”
Section: Introductionmentioning
confidence: 99%